The mRNA and Proteins Expression Levels Analysis of TC-1 Cells Immune Response to H9N2 Avian Influenza Virus - Liu, Jiyuan; Li, Ning; Meng, Dan; Hao, Mengchan; Wei, Liangmeng; Chai, Tongjie (Frontiers in Microbiology, 2016)
Since 1994, the H9N2 avian influenza has spread widely in mainland China, causing great economic losses to the poultry industry there. Subsequently, it was found that the H9N2 avian influenza virus (AIV) had the ability to infect mammals, which gave rise to great panic. In order to investigate the immune response of a host infected with H9N2 AIV, TC-1 cells were set as a model in this research. Quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) methods were used to study the expression changes of pattern recognition receptors (PRRs), inflammatory cytokines, and chemokines in AIV-infected TC-1 cells. Our research found that TC-1 cells had similar susceptibility to both CK/SD/w3 and CK/SD/w4 H9N2 isolates, while the CK/SD/w3 isolate had a stronger capability of replication in the TC-1 cells. At the same time, the expression of PRRs (MDA-5), cytokines (IL-1β and IL-6), and chemokines (RANTES and IP-10) were significantly up-regulated. These results indicated that MDA-5, IL-1β, IL-6, RANTES, and IP-10 might play important roles in the host immune response to H9N2 AIV infection. This study provided useful information for further understanding the interaction between H9N2 virus infection and host immunity, and had certain guiding significance for the prevention and treatment of this disease.